Current Trends in the Use of Patient-Reported Outcome Instruments in Degenerative Cervical Spine Surgery. (May 2016) - Ueda, Haruki; Cutler, Holt S.; Guzman, Javier Z.; Cho, Samuel K.
Study Design: Bibliometric analysis. Objective: To determine trends, frequency, and distribution of patient-reported outcome instruments (PROIs) in degenerative cervical spine surgery literature over the past decade. Methods: A search was conducted via PubMed from 2004 to 2013 on five journals ( The Journal of Bone and Joint Surgery, The Bone and Joint Journal, The Spine Journal, European Spine Journal, and Spine ), which were chosen based on their impact factors and authors' consensus. All abstracts were screened and articles addressing degenerative cervical spine surgery using PROIs were included. Articles were then analyzed for publication date, study design, journal, level of evidence, and PROI trends. Prevalence of PROIs and level of evidence of included articles were analyzed. Results: From 19, 736 articles published, 241 articles fulfilled our study criteria. Overall, 53 distinct PROIs appeared. The top seven most frequently used PROIs were: Japanese Orthopaedic Association score (104 studies), visual analog scale for pain (100), Neck Disability Index (72), Short Form-36 (38), Nurick score (25), Odom criteria (21), and Oswestry Disability Index (15). Only 11 PROIs were used in 5 or more articles. Thirty-three of the PROIs were appeared in only 1 article. Among the included articles, 16% were of level 1 evidence and 32% were of level 4 evidence. Conclusion: Numerous PROIs are currently used in degenerative cervical spine surgery. A consensus on which instruments to use for a given diagnosis or procedure is lacking and may be necessary for better communication and comparison, as well as for the accumulation and analysis of vast clinical data across multiple studies.